Development of Human Blood Circulation Board Media (PAPEDA) Oriented to Students' Mastery of Science Concepts - Asri Fauzi; Ida Ermiana; Aisa Nikmah Rahmatih; Ilham Handika; Awal Nur Kholifatur Rosyidah (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce human blood circulation board media (PAPEDA) based on validity, practicality and effectiveness regarding students' mastery of science concepts. This research is development research. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 25 grade 5 students at SDN 14 Cakranegara. The instruments used were validation sheets, teacher assessment sheets, student assessment sheets, and test questions for students' mastery of science concepts. The data analysis technique used is a validity test with the minimum criteria being in the valid category, then a practicality test based on the results of teacher assessment and student assessment with the minimum standards being in the practical type, and an effectiveness test with the criterion that the proportion of students who achieve the classical minimum completeness criteria is at least at 75%. This research shows that PAPEDA learning media meets valid criteria with an average expert assessment score of 84% with perfect measures. The results of field trials show that PAPEDA learning media meets practical and influential standards. The functional aspect assessment was obtained from teacher and student assessments, with average scores of 96% (efficient) and 81% (efficient). The effectiveness aspect is evaluated from the results of students' mastery of science concepts tests. The proportion of students who reach the minimum completeness criteria in the science concept mastery test is 80%, within the effective criteria. Thus, the learning media developed meets valid, practical and influential standards